Extraction of chlorophyll a from green leaves and its uses as chromophorwe in ultraviolet-visible spectroscopy - Siti Ainie Abd. Rahim, 1987-; Azli Sulaiman, supervisor; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2009